O estudo de Induções e Recorrências - uma abordagem para o Ensino Médio - Costa, Antonio Carlos de Lima (2015)
This work presents a research on the Induction Principles and the Recurrences, its history, mathematical concepts and applications used. Were developed some statements of Induction Principle and the Recurrences using some basic concepts from Number Theory, Combinatorics, Geometry and Set Theory that can be explored in high school. Was submitted a few activities that can be applied in the classroom of the high school in the development of mathematical concepts such as Arithmetic Progression, Geometric Progression, Geometry, Combinatorial Analysis and Numeric Sets among other topics.